Tetrahydrocurcumin inhibits HT1080 cell migration and invasion via downregulation of MMPs and uPA - Yodkeeree S. (2014)
Aim:Tetrahydrocurcumin (THC) is an active metabolite of curcumin. It has been reported to have similar pharmacological activity to curcumin. The proteases that participate in extracellular matrix (ECM) degradation are involved in cancer cell metastasis. The present study investigates the effect of an ultimate metabolite of curcumin, THC, on the invasion and motility of highly-metastatic HT1080 human fibrosarcoma cells.Methods:The effect of THC on HT1080 cell invasion and migration was determined using Boyden chamber assay. Cell-adhesion assay was used for examining the binding of cells to ECM molecules. Zymography assay was used to analyze the effect of THC on matrix metalloproteinase (MMP)-2, MMP-9, and urokinase plasminogen activator (uPA) secretion from HT1080 cells. Tissue inhibitor of metalloproteinase (TIMP)-2 and membrane-type 1 matrix metalloproteinase (MT1-MMP) proteins levels were analyzed by Western blotting.Results:Treatment with THC reduced HT1080 cell invasion and migration in a dose-dependent manner. THC also decreased the cell adhesion to Matrigel and laminin-coated plates. Analysis by zymography demonstrated that treatment with THC reduced the levels of MMP-2, MMP-9, and uPA. THC also inhibited the levels of MT1-MMP and TIMP-2 proteins detected by Western blot analysis.Conclusion:Our findings revealed that THC reduced HT1080 cell invasion and migration. The inhibition of cancer cell invasion is associated with the downregulation of ECM degradation enzymes and the inhibition of cell adhesion to ECM proteins. © 2008 CPS and SIMM.